Ritual Wuat Wa`I Di Desa Barang, Kecamatan Cibal, Kabupaten Manggarai Sebagai Model Penguatan Profil Pelajar Pancasila Di SMA - Both, Lusitiana; Purnawati, Desak Made Oka; Arta, Ketut Sedana (Universitas Pendidikan Ganesha, 2025)
This research aims to examine the history of the Wuat Wa’i tradition, understand the social processes of the community in Barang Village, Cibal District, Manggarai Regency in obtaining financial support through the Wuat Wa’i ritual, and identify models that can be developed to strengthen the Pancasila Student Profile at the Senior High School (SMA) level. The approach used in this research is descriptive qualitative, aiming to provide an in-depth description of the ongoing social phenomenon. The data sources used in this study are divided into two types: primary data and secondary data. The technique for determining informants applied is purposive sampling, which is the intentional selection of informants based on specific criteria relevant to the research focus. The research findings reveal several main discoveries: 1) The Wuat Wa’i tradition is essentially a cultural practice carried out as a form of prayer to God through the intercession of ancestors, which is manifested in the teing hang ise empo event (feeding the ancestors). This tradition initially involved only family members, where financial contributions were made voluntarily without coercion. Over time, this practice evolved into a fundraising event to support children's education and is known as the school party. 2) The implementation of the Wuat Wa’i ritual involves six sacred rites, including: calling the spirits of ancestors through prayers at the graves, rahi lonto leok (a greeting expression to guests), presenting tuak and cepa (arak and betel), the torok manuk Wuat Wa’i procession, toto urat, and helang (offerings for ancestors). 3) The model that can be developed in the context of strengthening the Pancasila Student Profile in high schools, based on the results of this research, includes values: faith and piety to God Almighty, mutual cooperation, critical reasoning, and noble character